Die Gleichstellung der Geschlechter im Lehrplan. Anregungen für Schule und Unterricht. - Bigga, Regine; Braun, F.; Hoffmann, L.

Erwerbsarbeit - Hausarbeit. Strukturwandel der Arbeit als Herausforderung an das Lernfeld Arbeitslehre - Tornieporth, G.; Bigga, Regine

Ergebnisse aus dem Projekt Mädchen & junge Frauen in der Arbeitswelt - Bigga, Regine (Erwerbsarbeit - Hausarbeit. Strukturwandel der Arbeit als Herausforderung an das Lernfeld der Arbeitslehre)

Electro-optic effect in polymer-dispersed cholesteric liquid crystals with medium chirality - Behrens, Ulrike; Kitzerow, Heinz-Siegfried; Chilaya, Gouram (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Bistability in polymer‐dispersed ferroelectric liquid crystals - Molsen, Henning; Kitzerow, Heinz-Siegfried (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Polymer-dispersed cholesteric liquid crystals - Crooker, Peter P.; Kitzerow, Heinz-Siegfried; Xu, F. (Liquid Crystal Materials, Devices, and Applications III)

Polymer-dispersed liquid crystals From the nematic curvilinear aligned phase to ferroelectric films - Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Director configurations of nematic-liquid-crystal droplets: Negative dielectric anisotropy and parallel surface anchoring - Xu, F.; Kitzerow, Heinz-Siegfried; Crooker, P. P. (Physical Review E)

A New Method to Align Smectic Liquid Crystals by Photo-Polymerization - Jain, Sukhmal C.; Kitzerow, Heinz-Siegfried (Japanese Journal of Applied Physics)
A novel technique to produce planar and homeotropic alignment of smectic liquid crystals is presented. The technique is based on producing an anisotropic polymer network in the bulk by photo-polymerizing a mixture of photoresist material and liquid crystal by linearly polarized UV-light. Both uniform planar alignment and homeotropic alignment can be obtained depending on the curing conditions. In the case of planar alignment, the orientation of liquid crystal molecules is governed by the direction of the polarization vector of the UV-light, thus making it possible to produce a defined azimuthal orientation of the liquid crystal director. This technique obviates the need to give any previous treatment to the bounding substrates.
Keywords: General Physics and Astronomy; General Engineering

Utility of a liquid crystalline diacrylate for bistable switching cholesteric gel displays - Behrens, Ulrike; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Bulk‐induced alignment of nematic liquid crystals by photopolymerization - Jain, Sukhmal C.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Characterization of Worm-like Micelles Containing Solubilized Dye-Molecules by Light Scattering Techniques - Herzog, Bernd; Huber, Klaus; Rennie, Adrian R. (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Mixtures of Polyacrylic Acid and Nonionic Surfactants at the Water/Air Interface - Maloney, Colette; Huber, Klaus (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Influence of scattering on the formation of Wannier-Stark ladders and Bloch oscillations in semiconductor superlattices - Meier, Torsten; von Plessen, G.; Feldmann, J.; Göbel, E.O.; Thomas, P.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Physical Review B)
We study the critical field for the formation of Wannier-Stark ladders and Bloch oscillations in GaAs/AlxGa1−xAs superlattices at low temperatures. From the results of photocurrent and transient four-wave mixing experiments, we conclude that the critical field is higher for superlattices with wide minibands than for superlattices, with narrow minibands. The explanation for this dependence is that intraminiband scattering due to LO-phonon emission is excluded in minibands narrower than the LO-phonon energy.

Coherent electric-field effects in semiconductors - Meier, Torsten; von Plessen, G.; Thomas, P.; Koch, S.W. (Physical Review Letters)
We present a microscopic analysis of coherent effects induced by electric fields in photoexcited semiconductors in the presence of the Coulomb interaction. Both the terahertz emission and four-wave-mixing signals arising from Bloch oscillations in a semiconductor superlattice are computed consistently. It is predicted that Bloch oscillations should be observable also for miniband widths on the order of the exciton binding energy.

Coherent Dynamics of Exciton Wavepackets in Semiconductor Heterostructures - Meier, Torsten; Koch, M.; Feldmann, J.; Göbel, E.O.; Jahnke, F.; Schäfer, W.; Thomas, P.; Koch, S.W.; Nickel, H.; Luttgen, S.; Stolz, W. (Proceedings der 8. International Winterschool on New Developments in Physics)
The coherent dynamics of exciton wavepackets in (GaIn)As/GaAs as well as (GaIn)As/Ga(PAs) multiple quantum well structures is studied by means of transient four-wave mixing (FWM) experiments. The wavepackets are generated by simultaneous excitation of several exciton transitions with laser pulses of about 100 fs duration. The time-integrated FWM signals exhibit a pronounced modulation superimposed on the overall decay which can be attributed to the quantum interference of the different eigenstates. In the time-resolved FWM signals this interference is not present, reflecting the interplay between many-body Coulomb effects and inhomogeneous broadening. This experimental technique is then employed to extract the exciton binding energies in pseudomorphic symmetrically strained (GaIn)As/GaIPAs) with various In contents.

Vertical transport studied by sub-picosecond four-wave mixing experiments - Meier, Torsten; Feldmann, J.; von Plessen, G.; Thomas, P.; Göbel, E.O.; Goosen, K.W.; Miller, D.A.B.; Cunningham, J.E. (Coherent Optical Interactions in Semiconductors)
Since the realization of semiconductor heterostructures vertical transport of electrically injected carriers has been one of the most interesting topics in semiconductor physics. Precise engineering of semiconductor layers and thus electronic energy levels allows the tailoring of transport properties over a wide range and has even led to the invention of semiconductor devices relying on ballistic electron transport. In addition, negative differential resistance (NDR) can be realized by using tunneling diodes containing double-barrier heterostructures or a superlattice structure.5,6 Actually, the proposal of Esaki and Tsu5 to use electronic Bloch oscillations in the miniband of a semiconductor superlattice to realize NDR marked the starting point for the physics and applications of semiconductor heterostructures.

Theory of polarization-dependent four-wave mixing using the optical Bloch equations - Meier, Torsten; Bennhardt, D.; Thomas, P.; Hu, Y.Z.; Binder, R.; Koch, S.W. (Coherent Optical Interactions in Semiconductors)
Transient four-wave mixing (TFWM) experiments have been widely used to study the excitation dynamics of excitons in quantum wells [1]. Recently is has been observed that TFWM signals, especially quantum beats between heavy-hole (hh) and light-hole (lh) excitons, strongly depend on the polarization of the incident laser pulses [2–6]. This dependence is presently being investigated.

Evidence of Biexcitonic Contributions to Four-wave-mixing in GaAs Quantum Wells - Meier, Torsten; Mayer, E.J.; Heuckeroth, V.; Smith, G.O.; Kuhl, J.; Bott, K.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Physical Review B)
A three-pulse degenerate four-wave-mixing experiment and its theoretical analysis reveal contributions of local field and biexciton effects to the nonlinear optical response of the two-dimensional exciton. Quantum beats with a frequency equivalent to the biexciton binding energy appear only for specific polarizations. Polarization-dependent spectrally resolved four-wave mixing shows an additional peak that is separated from the 1s heavy-hole exciton line by the biexciton binding energy. These experimental results are in good agreement with the optical selection rules of the theoretical model, providing evidence for biexcitonic contributions to the four-wave mixing.

Simultaneous influence of disorder and Coulomb interaction on photon echoes in semiconductors - Meier, Torsten; Jahnke, F.; Koch, M.; Feldmann, J.; Schäfer, W.; Thomas, P.; Koch, S.W.; Göbel, E.O.; Nickel, H. (Physical Review B)
The effects of disorder and many-body interaction on the four-wave-mixing signal in semiconductor quantum wells are studied experimentally and theoretically. For weakly disordered samples it is shown that the combined influence of Coulomb and disorder effects leads to a characteristic photon-echo signal in time-resolved measurements and to oscillations in the time-integrated signal. Convincing agreement between experiment and theory is demonstrated.

Intrinsic perturbations of Bloch oscillations and Wannier Stark ladders in semiconductor superlattices - Meier, Torsten; von Plessen, G.; Feldmann, J.; Thomas, P.; Göbel, E.O.; Koch, S.W. (Optics and Photonics News)

Contributions of Bound and Unbound Two-Exciton States to the Nonlinear Optical Response of GaAs Quantum Wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bennhardt, D.; Schulze, A.; Thomas, P.; Hey, R.; Ploog, K. (International Conference on Ultrafast Phenomena)
The strong influence of exciton/exciton interaction on the nonlinear optical response of the 2D exciton in GaAs quantum wells has been demonstrated in several recent experimental studies. The theoretical model for the microscopic coupling mechanism is still the subject of controversy, however. In ref. [1], we have presented a model including a density dependent coupling between opposite spin excitons which assumes that the interaction results in a renormalization of the matrix elements, dephasing rates and energies of the transition from the single-exciton state to the two-exciton state with respect to the corresponding quantities for the single exciton transitions. In contrast, Wang et al. claim that all experimental observations are explained by a density induced dephasing rate and that biexciton states play no role [2]. Here we present a new 3-pulse degenerate-four-wave-mixing (DFWM) configuration which is able to differentiate between pure local field effects and biexcitonic contributions to the time-integrated signal. Experiments were performed on an almost homogeneously broadened GaAs/Al0.3Ga0.7As single QW (well width 20 nm, photoluminescence line 0.3 meV, homogenous linewidth 0.15 meV) in the backward reflection geometry. The sample was cooled to 10 K and excited by a sequence of three pulses (1.1 ps duration) with equal intensity, wave vectors 𝑘→1,𝑘→2,𝑘→3 and delays τ12 and τ13 between the second and first and the third and first pulse, respectively. The signal was monitored in the direction 𝑘→𝑠=𝑘→1+𝑘→2−𝑘→3 which provides no signal for the chosen pulse length if local field and renormalization effects are negligible. The peak intensity of the time-integrated DFWM signal has been calculated by solving the optical Bloch for a system of two non-interacting two-level systems (2LS) with opposite circular polarization selection rules (local field effect) and for the renormalized four-level system (4LS) depicted in Fig. 1 which assumes the formation of biexcitons between excitons with opposite spins. The signal strength is proportional to the strength of the local field in the case of the 2LS and to the renormalization for the 4LS. The peak signal intensities expected for pure local field and pure biexction contributions are summarized in the second and third column of Table 1 for eight experimental configurations applying different linear and circularly polarized pulses. The values are normalized to the signal strength predicted for three parallel linearly polarized pulses. Close inspection of the data reveals remarkable differences of the peak amplitude with polarization geometry for the two coupling models.

Polarization selection rules for quantum beating between light and heavy holes in GaAs quantum wells - Meier, Torsten; Mayer, E.J.; Smith, G.O.; Kuhl, J.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Proceedings of the 5th European Quantum Electronics Conference)
Several recent experimental and theoretical studies have demonstrated the importance of exciton/exciton coupling due to Coulomb interactions for the nonlinear optical response of the 2D exciton in GaAs quantum wells (QWs).1,2 These results imply that multilevel models are required in order to provide a theoretically appropriate description of the nonlinear behavior. Previous application of a renormalized 9-level system has proven successful in describing the third-order response of hh-excitons in GaAs quantum wells.2 We present a comprehensive experimental and theoretical investigation of the polarization selection rules for degenerate- four-wave-mixing (DFWM) and quantum beating of hh and lh transitions in a GaAs QW. Depending on the polarization and temporal sequence of the three pulses simultaneous excitation of the hh and lh transitions generates either quantum beats (QB), no modulation of the signal, or a superposition of QB and polarization interference (PI) effects as proved by spectrally resolved (SR)-DFWM.

Observation of Biexcitons in Time-Resolved Degenerate-Four-Wave-Mixing on GaAs Quantum Wells - Meier, Torsten; Mayer, E.J.; Smith, G.O.; Kuhl, J.; Bennhardt, D.; Schulze, A.; Thomas, P.; Hey, R.; Ploog, K. (International Conference on Ultrafast Phenomena)
Although the importance of exciton/exciton interactions for the nonlinear optical response of GaAs quantum wells (QW) is well established by many experimental observations, the role of biexciton states in these processes is still an open question, even at low excitation densities. Evidence for the formation of biexcitons has been independently derived from pump-probe studies [1], from the density dependence of the photoluminescence (PL) line shape [2] and from signal modulations observed in degenerate-four-wave-mixing (DFWM) with incoherent light pulses [3]. Here, we report on time-resolved DFWM with parallel (PP) and cross-polarized (CP) pulses. Depending on the polarization geometry, the signals reveal strong quantum beats which correspond to the splitting between either the heavy hole (hh) and light hole (lh) exciton or the hh exciton and the biexciton.

Determination of excitonic binding energies in symmetrically strained (GaIn)As/Ga(PAs) multiple quantum wells using quantum beat spectroscopy - Meier, Torsten; Koch, M.; Stolz, W.; Feldmann, J.; Thomas, P.; Göbel, E.O. (Proceedings der 7. International Conference on Superlattices, Microstructures and Microdevices)
We have performed sub-picosecond four-wave mixing experiments on a series of symmetrically strained (GaIn)As/Ga(AsP) multiple quantum wells. We show that these measurements allow a precise determination of exciton binding energies. One of the advantages of this quantum beat method as compared to linear optical methods is that a determination of the exciton binding energy is possible even in the presence of considerable inhomogeneous broadening. In addition, the dependence of the exciton binding energy on the strain in the (GaIn)As quantum well layers suggests that the reduced electron-hole effective mass is not influenced by the increase in strain.

Field-induced dynamics of a wave packet in a wide superlattice miniband - Meier, Torsten; von Plessen, G.; Feldmann, J.; Göbel, E.O.; Thomas, P.; Goossen, K.W.; Kuo, J.M.; Kopf, R.F. (International Quantum Electronics Conference)
In the absence of scattering mechanisms, a crystal electron subjected to a homogeneous electric field undergoes a periodic motion in both momentum and real space. This oscillatory motion is known as Bloch oscillations (BOs) and has recently been detected in transient four-wave mixing (FWM) and Tera-Hertz emission experiments on semiconductor superlattices. It is generally assumed that the minimum field required for the observation of BOs is controlled by the rate of scattering in the material. However, an experimental verification of this point is still lacking.

Direct verification of the existence of biexcitons in GaAs qauntum wells - Meier, Torsten; Smith, G.O.; Mayer, E.J.; Kuhl, J.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (European Quantum Electronics Conference)
The strong nonlinear optical response of the 2D exciton in GaAs quantum wells at relatively low excitation densities has been observed in many experimental studies in accordance with theoretical predictions. In principle, exciton/exciton interaction results in a renormalization of the transition matrix elements, dephasing rates and frequencies of the excitonic states. Wang et al.1 claimed that all experimental results can be explained by a density- induced enhanced dephasing rate. In a previous paper,2 we have suggested a density dependent coupling between opposite spin excitons, which involves all three renormalization phenomena.

Interplay Between Inhomogeneous Broadening and Coulomb Interaction in the Dynamics of Excitonic Wave Packets - Meier, Torsten; Koch, M.; Jahnke, F.; Feldmann, J.; Schäfer, W.; Thomas, P.; Koch, S.W.; Göbel, E.O.; Nickel, H.
A proper description of subpicosecond four-wave-mixing (FWM) experiments for excitonic transitions in semiconductor heterostructures must consider the fact that the spectrally broad laser pulses excite not only the 1s bound exciton state but also energetically higher bound exciton states and the lower-lying part of the unbound continuum states. In this paper, we report results of transient and time-resolved FWM-experiments in which such ’excitonic wave packets’ play a crucial role. In addition, a theoretical treatment of the problem based on the solution of the semiconductor Bloch is presented. We show that the time-dependent nonlinear response is determined by an interplay between inhomogeneous broadening and Coulomb interaction.

Chemisorption of aluminium on GaAs(110) - Schmidt, Wolf Gero; Srivastava, G P (Journal of Physics: Condensed Matter)

AB initio calculation of the atomic and electronic structure for Sb adsorbed on GaAs(110) - Schmidt, Wolf Gero; Wenzien, Bernd; Bechstedt, Friedhelm (Czechoslovak Journal of Physics)

2H NMR study on the lyomesophases of the system hexaethylene glycol dodecyl methyl ether/water Temperature dependence of quadrupole splittings - Schnepp, W.; Disch, S.; Schmidt, Claudia (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Two-dimensional proton NMR studies of the conformations and orientations of n-alkanes in a liquid-crystal solvent - Rosen, M. E.; Rucker, S. P.; Schmidt, Claudia; Pines, A. (The Journal of Physical Chemistry)
Keywords: Physical and Theoretical Chemistry; General Engineering

Electric field effects on the droplet structure in polymer dispersed cholesteric liquid crystals - Kitzerow, Heinz-Siegfried; Crooker, P. P. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Observation of blue phases in chiral networks - Kitzerow, Heinz-Siegfried; Schmid, H.; Ranft, A.; Heppke, G.; Hikmet, R. A. M.; Lub, J. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Anomalies of the temperature dependence of electrostriction in blue phases - Dolganov, V. K.; Lourie, O. R.; Heppke, G.; Kitzerow, Heinz-Siegfried (Journal de Physique II)
Keywords: Physics and Astronomy (miscellaneous); General Engineering; Atomic and Molecular Physics; and Optics

UV-cured cholesteric polymer-dispersed liquid crystal display - Kitzerow, Heinz-Siegfried; Crooker, P. P. (Journal de Physique II)
Keywords: Physics and Astronomy (miscellaneous); General Engineering; Atomic and Molecular Physics; and Optics

Electrooptics of Polymer-Dispersed Ferroelectric Liquid Crystals - Molsen, H.; Bardon, R.; Kitzerow, Heinz-Siegfried (SID Conference Proceedings, 13th International Display Research Conference)

Electroclinic Effect in a Polymer-Dispersed Ferroelectric Liquid Crystal - Heppke, G.; Kitzerow, Heinz-Siegfried; Molsen, H. (Molecular Crystals and Liquid Crystals Science and Technology. Section A. Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics

First Observation of Selective Reflection and Blue Phases in Chiral Discotic Liquid Crystals - Krüerke, D.; Kitzerow, Heinz-Siegfried; Heppke, G.; Vill, V. (Berichte der Bunsengesellschaft für physikalische Chemie)
Keywords: General Chemical Engineering

Metallomesogens with a Cholesteric Mesophase - Baena, Maria J.; Buey, Julio; Espinet, Pablo; Kitzerow, Heinz-Siegfried; Heppke, Gerd (Angewandte Chemie International Edition in English)
Keywords: General Chemistry; Catalysis

Subpicosecond photon-echo spectroscopy on GaAs/AlAs short-period superlattices - Meier, Torsten; Koch, M.; Weber, D.; Feldmann, J.; Göbel, E.O.; Schulze, A.; Thomas, P.; Schmitt-Rink, S.; Ploog, K. (Physical Review B)
We present subpicosecond time-resolved four-wave-mixing studies on GaAs/AlAs short-period superlattices having different miniband widths. Photon echoes are observed as a consequence of the inhomogeneous broadening of the excitonic resonance. In addition, the photon-echo signal exhibits periodic modulations as a function of the time delay between the excitation laser pulses. Free excitons and excitons bound to neutral acceptors are identified as the underlying three-level system leading to the observed photon-echo quantum beats. From the beat period we can directly infer the dissociation energy of the bound exciton. In accordance with theory, we find that the dissociation energy decreases with increasing miniband width, i.e., when the excitons become less confined. In addition, we find that the dephasing rate of bound excitons is about one order of magnitude less than that of free excitons and is mainly determined by energy relaxation.

Time resolved Four Wave Mixing in GaAs/AlAs Quantum Well Structures - Meier, Torsten; Göbel, E.O.; Koch, M.; Feldmann, J.; von Plessen, G.; Schulze, A.; Thomas, P.; Schmitt-Rink, S.; Köhler, K.; Ploog, K. (Optical Phenomena in Semiconductor Structures of Reduced Dimension)
Femtosecond nonlinear laser spectroscopy is applied to study the dynamics of coherent optical excitations in semiconductors. In particular, beat phenomena of excitonic excitations in quantum wells and superlattice structures will be considered. We will demonstrate that four wave mixing experiments with time resolved detection of the nonlinear signal are able to distinguish between quantum beats and polarization interference. In addition, we report for a GaAs/AlAs superlattice the observation of quantum beats in the photon echo signal. The occurence of these beats is attributed to the simultaneous excitation of bound and localized excitons.

Coherent Dynamics of Excitonic Wave Packets - Meier, Torsten; Feldmann, J.; von Plessen, G.; Koch, M.; Göbel, E.O.; Thomas, P.; Bacher, G.; Hartmann, C.; Schweizer, H.; Schäfer, W.; Nickel, H. (Physical review letters)
We report on the coherent dynamics of excitonic wave packets observed in transient four-wave mixing experiments on strained InGaAs/GaAs quantum-well structures. The excitonic noneigenstates are created by using laser pulses shorter than the electron round trip time within the exciton orbital. A characteristic temporal modulation of the diffracted signal is observed, which resembles the coherent dynamics of an electron wave packet in a hydrogen atom expected for the case of a simultaneous excitation of all bound and the lowest continuum states.

Dipole-dipole coupling of excitons in double quantum wells - Meier, Torsten; Batsch, M.; Thomas, P.; Lindberg, M.; Koch, S.W.; Shah, J. (Physical Review B)
Exciton coupling is studied for double quantum wells, which are separated by thick barriers. Results are presented for the linear optical spectrum, stationary and transient luminescence as well as four-wave-mixing signals. Additionally, coherent and incoherent transport through the barrier is considered

Theory for polarization-dependent four-wave-mixing signals in quantum wells - Meier, Torsten; Bennhardt, D.; Thomas, P.; Eccleston, R.; Mayer, E.; Kuhl, J. (Quantum Electronics and Laser Science Conference)
In degenerate four-wave-mixing (DFWM) experiments the polarization of the incident laser pulses can have a strong influence on the measured signal. For GaAs quantum wells a number of DFWM experiments were performed by using either parallel or perpendicular polarization of the incident laser pulses. Experimentally, it turned out that some characteristic features of the signal differ appreciably for the two configurations. In particular, different dephasing times, phase shifts of the quantum beats, different time-resolved behavior (echoes versus free-induction decay), and intensity dependence of the measured signal have been reported

Coherent coupling of exciton transitions in semiconductor quantum structures - Meier, Torsten; Koch, M.; Feldmann, J.; von Plessen, G.; Schulze, A.; Göbel, E.O.; Thomas, P.; Schmitt-Rink, S.; Shah, J.; Ploog, K.; Köhler, K. (Quantum Electronics and Laser Science Conference)
We investigate the coherent coupling of free and bound excitonic transitions, as wets as of distinct excitonic transitions arising from spatially separated quantum-well islands by means of time-resolved four-wave-mixing experiments.

Forschungsergebnisse zur Geschlechterfrage - Konsequenzen für die Gestaltung von Unterricht sowie für die Aus- und Weiterbildung von Lehrkräften - Bigga, Regine (Lehrplanrevision in Schleswig-Holstein)

Chromaticity of polymer-dispersed cholesteric liquid crystals - Kitzerow, Heinz-Siegfried; Crooker, P. P.; Heppke, G. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Behaviour of polymer dispersed cholesteric droplets with negative dielectric anisotropy in electric fields - Kitzerow, Heinz-Siegfried; Crooker, P. P. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Microscopic observations of axial and radial nematic droplets for a dual-frequency addressable liquid crystal - Kitzerow, Heinz-Siegfried; Xu, F.; Crooker, P. P. (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry